Nonresonant and Resonant Spin Rectification in the Exchange Biased NiFe/MnIr Bilayer. Issue 9 (10th June 2018) - Pan, Lining; Soh, Wee Tee; Phuoc, Nguyen N.; Ong, Chong Kim
Abstract : Through a systematic investigation of the magnetization rotation and reversal in an exchange‐biased NiFe/MnIr film electrically detected by spin rectification effect (SRE), we experimentally demonstrate that this SRE DC voltage can be detected in the field‐swept spectra both at resonant and nonresonant conditions. The spectra show clear shifted hysteretic curves driven by exchange bias and a hysteresis loop is formed at applied magnetic field around exchanged bias field by the nonzero SRE DC voltage with sign change with the sweeping direction. More interestingly, we found that the voltage magnitude changes upon switching of magnetization can be greatly enhanced at resonance thereby suggesting an attractive approach to realize a highly sensitive method to measure exchange bias field. This experimental behavior can be interpreted within the framework of the near‐resonant spin rectification effect. Abstract : Pan et al. have investigated the nonresonant and resonant spin rectification in the exchange biased NiFe/MnIr bilayer. The hysteretic rectified DC loops shifted by exchange bias effect towards the negative H axis. From this, one can obtain the exchange bias field and coercivity field consistent with vibration sample magnetometer measurements. This implies that the spin rectification effect DC voltage can be used to study magnetization rotation behavior.